PROBLEMS OF USE OF ADMINISTRATIVE INFORMATION SOURCES IN MACROECONOMIC STATISTICS - A. Abroskin; N. Abroskina (Вестник университета)
The article concerns the topical issues of the information base of strategic planning and management of the economy extension on the basis of using the administrative data sources. The article considers the problems of convergence of the administrative and statistical indicators methodological base, features of harmonization of applied definitions, matching of the boundaries of structural units and systems of used classifiers relating to different accounting systems. In addition organizational mechanisms for data acquisition from administrative sources are considered.